2008
DOI: 10.1063/1.2894507
|View full text |Cite
|
Sign up to set email alerts
|

Fluorination-induced magnetism in boron nitride nanotubes from ab initio calculations

Abstract: Articles you may be interested inTransverse dielectric properties of boron nitride nanotubes by ab initio electric field calculations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 27 publications
2
56
0
Order By: Relevance
“…[8] However, the methods to prepare BNNSs are fewer and less effective than that of graphene, which is partially due to the stronger interactions among neighboring hexagonal boron nitride (h-BN) layers that make the exfoliation of BNNSs from bulk h-BN more difficult than peeling off graphene from graphite. For example, Li et al [16] predicted that the chemisorption of fluorine atoms onto the boron atoms in BNNT can induce spontaneous magnetization. [13][14][15] The published studies on the possible magnetic properties of fluorinated BNNSs (F-BNNSs) or boron nitride nanotubes (F-BNNTs) are of theoretical nature.…”
mentioning
confidence: 99%
“…[8] However, the methods to prepare BNNSs are fewer and less effective than that of graphene, which is partially due to the stronger interactions among neighboring hexagonal boron nitride (h-BN) layers that make the exfoliation of BNNSs from bulk h-BN more difficult than peeling off graphene from graphite. For example, Li et al [16] predicted that the chemisorption of fluorine atoms onto the boron atoms in BNNT can induce spontaneous magnetization. [13][14][15] The published studies on the possible magnetic properties of fluorinated BNNSs (F-BNNSs) or boron nitride nanotubes (F-BNNTs) are of theoretical nature.…”
mentioning
confidence: 99%
“…Previous investigations have shown that the adsorption of light element on carbon, BN, ZnO, and SiC nanotubes can induce magnetism (Hao et al 2006;Li et al 2008Li et al , 2009Lii et al 2008;Meng et al 2007;Wu et al 2005;Zhang and Guo 2009;Zhao and Ding 2008b). Next we systematically discuss the electronic and magnetic properties of the Li adsorption on SiC nanotubes.…”
Section: Resultsmentioning
confidence: 98%
“…BNNTs exhibit therefore clear magnetic properties, mainly due to the Fe catalyst particles used for promoting nanotube growth. However, we should not exclude possible weak magnetic properties of pure BNNTs caused by defects and impurities [24].…”
Section: Bnnt Magnetic Propertiesmentioning
confidence: 99%